Giant vulvar melanoma in an 89-year-old woman – case report and review of the literature - Gottwald, Leszek; Korczyński, Jerzy; Wójcik-Krowiranda, Katarzyna; Jakubik, Jarosław; Góra, Ewa; Bieńkiewicz, Andrzej (Menopause Review/Przegląd Menopauzalny, 2008)
Non-squamous malignant tumours of the vulva encompass an exciting and broad group, including Bartholin’s gland carcinoma, malignant melanoma, Paget’s disease, sarcomas and lymphoma. Vulvar melanoma is the second most common vulvar malignancy and represents an important women\'s health issue. Overall, melanomas of the vulva account for 2-10% of all malignancies of the female external genitalia. Due to the rarity of this disease, the mode of treatment recommendations are not established as yet. We report a case of an 89-year-old woman with giant melanoma of the vulva. A review of the literature connected to vulvar melanoma is presented as well.